ANALISIS NET PROFIT MARGIN DAN FREE CASH FLOW TERHADAP EARNING MANAGEMENT SEKTOR INDUSTRI BARANG KONSUMSI - Lyandra Aisyah Margie; Habibah Habibah (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine the effect of net profit margin and free cash flow on earning management. The population in this study are consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the period 2016 to 2019. The number of samples in this study was 64 respondents, using the purposive sample method. The research approach used is quantitative. The analytical method used is multiple linear regression. The results showed that simultaneously, net profit margin and free cash flow had a significant effect on earnings management in the consumer goods industry sector. However, partially, only free cash flow has a significant effect on earnings management, while net profit margin does not significantly affect earnings management in the consumer goods industry sector.